Simulation of complex systems - Argun, Aykut; Callegari, Agnese; Volpe, Giovanni (Physicist) (IOP (Series). Release 21., 2021)
This book deals with the most fundamental and essential techniques to simulate complex systems, from the dynamics of molecules to the spreading of diseases, from optimization using ant colonies to the simulation of the Game of Life.